Analysis of the Effectiveness of Platelet-Rich Plasma in the Treatment of Discogenic Pain Syndrome of the Lumbar Spine - Chervatiuk, M.S.; Fishchenko , Ya.V. (TERRA ORTHOPAEDICA, 2025)
Objective. This study aims to evaluate the effectiveness of intradiscal injection of platelet-rich plasma (PRP) in the treatment of discogenic pain syndrome of the lumbar spine. Materials and Methods. The study was conducted from July 2022 to September 2024 at the SI “Institute of Traumatology and Orthopedics of NAMS of Ukraine.” Patients diagnosed with discogenic pain syndrome received intradiscal PRP injections. The effectiveness was assessed at 1 and 6 months post-treatment using the Visual Analog Scale (VAS), the Oswestry Disability Index (ODI), and MRI findings (Pfirrmann classification). Results. One month after the injection, VAS scores decreased by more than 3 points in 21.2% of patients, by 2 points in 18.1%, and by 1 point in 39.3%. Six months after the injection, VAS scores decreased by more than 3 points in 54.5% of patients, by 2 points in 12.2%, and by 1 point in 21.2%. On average, VAS scores decreased by 30% one month after injection and by 46% six months after treatment compared to baseline. The average ODI scores decreased to 8.06% one month after injection and to 6.67% six months after injection, respectively. MRI evaluation of intervertebral disc changes using the Pfirrmann classification did not reveal statistically significant differences but showed a tendency toward a reduction in degenerative changes 6 months after the injection. Conclusions. The use of platelet-rich plasma significantly reduced pain and improved quality of life in patients with discogenic pain syndrome who participated in the study 6 months after treatment initiation. It is also important to note that PRP therapy is safe due to the autologous nature of the product. Additionally, no clinically significant side effects or complications were observed. The results allow us to conclude that PRP therapy is effective in treating discogenic pain syndrome.